EDUKASI PENGOLAHAN SAMPAH DUSUN ABADI KECAMATAN BIREM BAYEUN ACEH TIMUR - Bukhari; Ramdan Afrian (Global Science Society, 2020)
The growth of settlements is rapidly signifying increasing citizen welfare. The same condition is also seen in the area of Birem Bayeun. The increase in population directly will affect the increase in landfills due to increased consumption of people. Things do the public in terms of garbage, so far only the form of gathering and disposal. The community only collects various kinds of garbage in one container. It is compounded by the absence of proper waste management. Intensive and ongoing efforts are needed to ensure that public awareness of the waste in their environment becomes high. One way to solve this is by introducing and implementing the 3R (Reduce, Reuse, Recycle) principle. By using this concept, people can utilize existing garbage so that it has economic value and selling power. It will eventually impact the reduction of waste in its environment. In order for this concept to run properly it is necessary to participate from the community in the implementation.